Graphene Functionalization and Nanopolymers - Silva, Martin Kássio Leme [UNESP] (2019)
This chapter focuses on the functionalization of graphene, mainly in graphene oxide (GO) and reduced graphene oxide (rGO). In this sense the main syntheses for obtaining GO and rGO, as well as their characterizations and applications, were described. To evaluate the electrochemical, spectrophotometric and morphological properties of functionalized graphene, the GO obtained commercially and the rGO synthesized by the chemical method using sodium borohydride were characterized by scanning electron microscopy, Raman, UV-vis, cyclic voltammetry and electrochemical impedance spectroscopy. Through these characterizations it is possible to comprehend the differences between GO and rGO. After that, the importance of the graphene functionalized in the development of electrochemical biosensors and sensors are presented.